Experimental Study Conducted Rendahsetelah Tenacity Carbon Steel Heat Treatment Austempering - Wijaya R D (International Conference on Engineering and Technology Development (ICETD), 2017)
The principle of this Austempering heat treatment is done by heating the steel to austenite tempratur then quenching the hot water bath salts ± 250-550 ° C and held at that time long enough so that the austenite transformed into bainite entirety. If the eutectoid steel is cooled rapidly in the austenite phase to a temperature between 250- 550 ° C and held at that temperature interval (isothermal) will be formed called bainite microstructure according to the name of the inventor, Dr. EC Bain. Bainite microstructure is the result of non-lamellar eutectoid reaction while perlite produced from lamellar eutectoid reaction. Bainite is a microstructure that is a mixture of ferrite phase and cementite (Fe3C). At a temperature of 350-550 ° C will be formed bainite top (upper bainite) while at 250-350 ° C will be formed under the bainite (lower bainite). In this study material used for heat treatment of austempering is low carbon steel with a solution of salt water quenching media. In this study austempering process carried out at a temperature of 300, 350, and 400 ° C with a holding time of 30 minutes. The results of this study indicate if low carbon steel austempering process is carried out hardness values decreased, namely from 144 to 116 at a temperature of 400 ° C, so the higher the austempering tempratur lower hardness value